Effect of two flow regimes on the upstream movements of the Iberian barbel (Luciobarbus bocagei) in an experimental pool‐type fishway. (8th October 2012) - Santos, J. M.; Branco, P. J.; Silva, A. T.; Katopodis, C.; Pinheiro, A. N.; Viseu, T.; Ferreira, M. T.
Summary Literature related to pool‐type fishways has seen a recent upsurge of interest in the placement of instream structures for improving fish passage. However, there is still no information on how different flow regimes created by boulder placement have an influence on upstream fish movements. The main goal of this study was to assess the performance of two different flow regimes, characterized by the relative depth of flow (d/h), where d is the water depth and h is the height of artificial bottom substrata, in assisting fish passage in an experimental full‐scale pool‐type fishway. Two series of experiments consisting of 20 replicates each and representing distinct flow regimes created by boulder placement in the flume bottom – d/h > 4 (regime 1) and 1.3 < d/h < 4 (regime 2) – were carried out to analyse the proportion and timing of successful upstream movements of a potamodromous cyprinid, the Iberian barbel (Luciobarbus bocagei). Although no significant differences (P > 0.05) in passage success were observed between regimes (55% and 60%, respectively), fish transit time was significantly lower (P < 0.05) in regime 2 (mean ± SD: 2.6 ± 1.6 min.) than in regime 1 (7.1 ± 5.8 min.). The results of these experiments show that lower relative depths can be more beneficial to fish passage because they reduce the transit time for successful negotiation, thus providing a useful indication on how to improve fish passage through pool‐type fishways.